The Effectivenessof E-Learning in Comprehending English Reading Text in MA Al-Karimiyyah - naily rif`atul aliyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This article is aimed at knowing the Effectivenessof E-Learning in Comprehending English Reading Text in MA Al-Karimiyyah. The     research design in this research is experimental research design. The subject of this research is the second class of senior high school n MA Al-Karmyyah. The instruments of this research are test administration and giving questionnaire. The result showed that there is no significant difference between control class and experimental class in using e-learning, but there is a difference between pre-test and post-test students score,  means that using e-learning at MA Al-Karimiyyah is not effective but shared reading method can increase students reading comprehension. It can be seen from the comparing the score of control class and try out class. From the data in the test which is using Independent sample T-test showed that the significant value 0.222 > 0.05, so the hypothesis is rejected. It also has the same result with the questionnaire which has the significant value 0.483 > 0.05.Key words: E-learning, offline learning, reading comprehension, google classroom